Application of Organic Fertilizer Dosages Results of Ampangsari Red Onion Varieties with Chilli - Yuliartini, Made Sri; Udayana, I Gusti Bagus; Kartini, Luh; Wirajaya , Anak Agung Ngurah Mayun; Sudewa, Ketut Agung; Sedana, Gede Yudi; Widyatna, I Komang (Formosa Journal of Applied Sciences, 2024)
A cultivation method called intercropping involves planting multiple plants in one location to optimize land functions that combine intensification and diversification. The aim of the research was to obtain growth and yield responses in shallot varieties intercropped with chilies when administering organic fertilizer doses, so as to obtain organic fertilizer doses for onion and chili varieties and develop them into the production system.    Research was conducted in the rice fields of Selat Village, Abiansemal, Badung.  The factorial RKA includes two components: the amount of organic fertilizer (D), four levels D1 = 10 tons per hectare; D2 = 20 tons per hectare; D3 = 30 tons per hectare; D0 = 0 tons per hectareDan Types, two taraf yaitu Super Philip is V1, and Bali Karet is V2.